Recommended Sweetpotato Farming Practices in Southeast Asia: A way to promote sustainable rural development and food security under a changing climate. - International Potato Center (International Potato Center, 2017)
This training manual describes CSA practices for sweetpotato, which aim to transform sweetpotato cultivation practice to sustainably support development and food security under a changing climate. This is a valuable resource for those involved in training extension workers, village leaders, and staff of IFAD investment projects FoodSTART+ collaborates with, among others; who will, in turn, train farmers and help them build their problem solving and decision-making skills so they can continue to learn, question, test and address different opportunities and challenges relevant to their livelihoods.